PRECEPTORSHIP METHOD TO THE ACHIEVEMENT OF NEW NURSE COMPETENCIES AT RUMAH SAKIT ISLAM SURABAYA JEMURSARI - yuliartiningsih yuliartiningsih; yanis kartini; nursalam nursalam (Universitas Nahdlatul Ulama Surabaya, 2019)
ABSTRACT Background: Competency issues and the lack of implementation of an orientation program with the preceptorship method are problems and require solutions / solutions. New nurses need the right information and well-structured learning to improve basic skills in implementing appropriate nursing care standards. The purpose of the study explained the influence of the preceptorship method to the achievement of new nurse competencies. Method: The design of this study used quasy-experiment by conducting the pre-test and post-test stages in the treatment and control groups. The design of the analysis variable was obtained by twenty new nurses from different units in RSIS Jemursari and RSI Surabaya using total sampling. The independent variable is the preceptorship method and the dependent variable is the achievement of new nurse competencies. The research instrument uses a checklist of competencies for new nurses based on basic competencies according to SKKNI. Data analysis using Paired Sample t Test and Independent Sample t Test with α = 0.05. Results: achievement of the competency of new nurses before and after intervention in the treatment group obtained Paired Sample t Test value = 0,000 <0,05 and the control group obtained the value of Paired Sample t Test = 0,000 <0,05 means that there is a significant influence before and after it is done the method of preceptorship towards achieving the competence of new nurses. Before the intervention in the treatment group and the control group, the Independent Sample t Test = 0.139 <0.05 means that there is no difference between the treatment group and the control group, whereas after intervention in the treatment and control groups obtained Independent Sample t Test = 0,000 <0.05 means that there is a difference between the treatment group and the control group after the preceptorship method is done. Discussion: The preceptorship method is a determinant variable that influences the achievement of new nurse competencies. Suggestions for hospitals to improve the quality of HR (preceptor) and the competence of new nurses, it is necessary to provide training in CE / preceptor. Keywords: Preceptorship, achievement of competence, new nurses.